THREE PROVOCATIONS FOR CIVIC CROWDFUNDING - Davies, Rodrigo (AoIR Selected Papers of Internet Research, 2014)
The rapid rise of crowdfunding in the past five years, most prominently among US- based platforms such as Kickstarter and IndieGoGo, has begun to attract the attention of a wide range of scholars, policymakers and practitioners. As the industry evolves, it is developing a range of specialist sub-genres and platforms, from politics to manufacturing. This paper considers civic crowdfunding – the use of crowdfunding for projects that produce community or quasi-public assets – and argues that its emergence demands a fresh set of questions and approaches.